Dynamics of Cultural Continuity and Transformation among Tharus in Surkhet - Ghanshyam Khadka; Mahesh Sharma (Surkhet Journal, 2025)
This study examines the dynamics of cultural continuity and transformation among the Tharu community of Tilpur in Nepal’s Surkhet District, addressing a critical gap in localised studies on indigenous identity amidst rapid socio-economic change. As one of the largest ethnic groups in the Terai region, the Tharus have long preserved a distinct cultural identity through unique traditions, language, and agrarian practices. However, modernisation, migration, education, and state policies now challenge this heritage. The study’s objectives are to (1) explore cultural continuity and change in Tharu traditions, (2) understand socio-economic impacts on livelihoods and social structures, and (3) explore cultural preservation challenges. This study employs an ethnographic approach, combining participant observation, key informant interviews with elders and local leaders, and household surveys (N=45) to triangulate qualitative and quantitative data. Findings reveal a dual reality: while festivals like Maghi and rituals endure, dress, language, family structures, and livelihoods increasingly reflect external influences. Economic shifts, from agriculture to wage labour and foreign employment, intersect with generational divides, as youth adopt Nepali language and non-Tharu customs, yet elders actively preserve traditions. Notably, the community demonstrates resilience by selectively adapting to change while sustaining core identity markers. This study contributes to debates on indigenous cultural resilience, illustrating how marginalized groups negotiate globalization’s pressures. It underscores the need for policies that support cultural preservation alongside equitable development, offering insights applicable to indigenous communities worldwide facing similar transitions.